(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Topical drug dosage forms such as ointments and creams can be easily removed through wetting, movement and contact. The new bioadhesive formulations with enhanced local anesthetic effects are needed for topical administration. The adhesive capacity of hydroxypropyl methylcellulose (HPMC) was determined by measuring the maximum detachment force and the adhesion work with an auto peeling tester. Topical delivery of Bupivacaine via various formulation approaches has been investigated in the present research work. Novel clear, stable, hydrogels, nanoemulsion based gels and metered dose film forming sprays of Bupivacaine base and its pharmaceutically acceptable HCl salt at 5% and 10% concentrations respectively for topical delivery has been developed and optimized. The formulations were developed to modulate the drug diffusion and accumulation at the intended site to exhibit the desired response. Topical hydrogels of Bupivacaine HCl were developed using co-solvents and penetration enhancers. The optimized hydrogels exhibited desired consistency, homogeneity, spreadabiltity and stability. Since, the polymers were water soluble; consequently, water washable gels were formed and offered benefits like ease of application and ease of removal.The bupivacaine gels containing both penetration enhancer and vasoconstrictor showed enhancement and prolonged efficacy compared to the control gel. To enhance the local anesthetic effects of bupivacaine, the transdermal bupivacaine gel formulation containing penetration enhancer and vasoconstrictor could be developed.